Spatial variability of phthalates contamination in the reef-building corals Porites lutea, Pocillopora verrucosa and Pavona varians. (June 2020) - Montano, Simone; Seveso, Davide; Maggioni, Davide; Galli, Paolo; Corsarini, Stefano; Saliu, Francesco
Abstract: Microplastic pollution represents a serious hazard for the marine environment, including coral reefs. Scleractinian corals can easily mistake microplastics with their natural preys, and ingest them and all the annexed plasticizer additives. Here we selectively searched on field for five phthalates esters (PAEs) namely dibutyl-phthalate (DBP), benzylbutyl-phthalate (BBzP), diethyl-phthalate (DEP), Bis(2-ethylhexyl)-phthalate (DEHP), and dimethyl-phthalate (DMP) in the coral species Pocillopora verrucosa, Porites lutea and Pavona varians . Our data reveal that >95% of corals sampled were contaminated, with a maximum of 172.4 ng/g, a value 7 time-fold higher than those found in a previous study. The Σ5 PAEs showed an average of about 30 ng/g per coral, but no differences in PAEs contamination was detected between species, depth or reef exposure. Despite their effects on coral physiology are not yet known, PAEs should be now considered as a novel, and ubiquitous, form of contamination in corals. Highlights: The three investigated species and 95% of investigated specimens showed contamination by phthalates. Porites lutea showed a value seven time higher than in previous study. Depth and exposure to wave action do not effect spatial distribution of PAEs. PAEs are widespread in Maldivian coral communities.